The impact of the Covid-19 pandemic on Indonesia's energy transition - Iva Rachmawati, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The COVID-19 pandemic has provided a positive impetus for the energy transition for several countries. With the lockdown policy, which causes a decrease in fossil energy consumption, fossil energy prices become unstable. The decreasing pollution level has made them increasingly aware of the need to encourage renewable energy. Increasing investment in renewable energy indicates that the energy transition is positive. This article examines Indonesia's energy transition, which has been affected by the COVID-19 pandemic, even though it has committed to achieving a mixed level of 23% by 2025. Through a literature review method regarding renewable energy policies during the pandemic and direct interviews with stakeholders related to renewable energy, this article claims that the impact of the Covid 19 pandemic on Indonesia's energy transition is insignificant. On the contrary, Indonesia experienced a slowdown in the energy transition during the pandemic. The downturn in the energy transition happened because previous policies regarding the energy sector did not favor renewable energy in Indonesia. Coal is still a strategic sector because of its cheap price and increasing demand. Investment and subsidies still favor the coal sector rather than renewable energy. The implication of this study is a change in government policy towards the energy transition through technology and investment for better energy security and the environment.